Congenital cytomegalovirus infection inducing non-congenital sensorineural hearing loss during childhood; a systematic review. (December 2018) - Riga, Maria; Korres, George; Chouridis, Pantelis; Naxakis, Stephanos; Danielides, Vasilios
Abstract: Background: Congenital cytomegalovirus (CMV) infection is one of the most important risk factors for delayed onset and progressive hearing loss in children. However, the relevant literature is limited, heterogeneous and currently insufficient to provide guidance toward the effective monitoring of hearing acuity in these children. Objectives: The aim of this study was to provide a systematic review focused on types of hearing loss that may escape diagnosis through universal neonatal hearing screening and/or present significant changes during childhood, such as progressive, fluctuating and late-onset hearing loss. Data sources: A review of the present literature was conducted via the PubMed database of the US National Library of Medicine (www.pubmed.org) and Scopus database (www.scopus.com) with the search terms "late-onset hearing loss cytomegalovirus", "progressive hearing loss cytomegalovirus" and "fluctuating hearing loss cytomegalovirus". Study eligibility criteria: Prospective or retrospective clinical studies were included if they presented a detailed audiological assessment, for a follow-up period of >2years. Methods: The prevalence and time of diagnosis of progressive, fluctuating and late-onset hearing loss were considered as primary outcomes. Results were recorded separately for symptomatic and asymptomatic children, when possible. Results: This analysis refers to a population of 181 children with CMV-induced hearing loss, who were diagnosed among 1089 with congenital CMV infection. The prevalence of CMV-induced hearing loss was significantly higher among symptomatic children (p < 0.0001), who were also significantly more likely to develop bilateral hearing loss (p = 0.001). There was not sufficient information on the prevalence, laterality, degree and time of diagnosis of progressive, fluctuating and late-onset hearing loss that could constitute the basis toward the report of specific follow-up guidelines. Conclusions: Further studies are needed in order to understand and quantify the potential effects of congenital CMV infection in the inner ear and hearing acuity. The results presented in the relative studies should be very carefully evaluated and compared to each other, since they correspond to substantially different cohorts, study designs, and result elaboration. Infants with congenital CMV infection should be closely monitored, regarding their hearing acuity at least during their preschool years, although substantial changes in hearing thresholds have been reported as late as the 16th year of age. Parental counseling is of outmost importance in order to minimize the numbers of children lost to follow-up.